Improving Operational Efficiency Through Digital Archiving: A Case Study of Debtor Document Management at BRI Regional Office Denpasar - Erin, Ni Putu; Wardani, Kadek Devi Kalfika Anggria; Gorda, Anak Agung Ngurah Eddy Supriyadinata (LPPM Universitas Jambi, 2025)
This study explores the digitalization of debtor document archives at BRI Regional Office Denpasar, aiming to address the inefficiencies of manual document management. Prior to this study, debtor document management was performed manually, resulting in delays in document retrieval and prolonged credit decision-making times. This study introduces a novel approach by implementing a digital archive system using spreadsheets, which significantly improves operational efficiency, document accessibility, and security. The methodology employed follows the PDCA (Plan, Do, Check, Action) cycle, which includes interviews, data collection, and iterative evaluations. The findings of this study show that digitalizing debtor documents significantly reduced retrieval times, enhanced the speed of credit decision-making, and streamlined administrative processes. The implementation of this system also allowed for real-time access to debtor documents, improving organizational control and document security. The study contributes to the literature by demonstrating the effectiveness of digital archiving in the banking sector and highlights the potential for broader adoption of digital solutions in similar financial institutions. The implications of this study suggest that digital archive systems can significantly enhance operational efficiency, improve service delivery, and ensure compliance with regulatory standards.